PELATIHAN SISTEM MONITORING MUTU REAL TIME: VISUALISASI BIG DATA SPMI BERBASIS CLOUD SEBAGAI STRATEGI MITIGASI PENURUNAN STATUS AKREDITASI DI SDN PONTANG KABUPATEN SERANG - Nuryati Nuryati; M. Syadeli Hanafi; Dewi Surani; Minhatul Maarif; Harry Budiman; Baehaki Baehaki; Ifa Hafiroh; Atikah Atikah; Minarti A; Anton Nasrullah (Yayasan Education and Social Center, 2026)
This community service activity aimed to improve the quality management system at SDN Pontang, Serang Regency through training on a cloud-based real-time quality monitoring system integrated with SPMI big data visualization. The activity was conducted in December 2025 using participatory methods consisting of observation, training, mentoring, implementation, and evaluation stages. Participants included school principals, teachers, school operators, and internal quality assurance teams. The training materials covered cloud computing, educational big data management, dashboard utilization, and real-time quality monitoring. The results showed significant improvements in participants’ digital competencies, especially in operating cloud-based quality dashboards, managing school quality data, and conducting data-driven evaluations. The implementation of the system also increased the effectiveness of quality monitoring, accelerated access to accreditation documents, and strengthened a sustainable data-based quality culture in schools. Furthermore, the cloud-based monitoring system enabled schools to identify declining quality indicators early and implement mitigation strategies systematically. This activity demonstrates that integrating cloud technology and SPMI big data visualization can serve as an innovative strategy to support accreditation readiness and improve educational quality management in elementary schools during the digital transformation era.